Surface and Buildup Region Dose Measurements with Markus Parallel-Plate Ionization Chamber, GafChromic EBT3 Film, and MOSFET Detector for High-Energy Photon Beams - Ugur Akbas; Nazmiye Donmez Kesen; Canan Koksal; Hatice Bilge (Advances in High Energy Physics)
The aim of the study was to investigate surface and buildup region doses for 6 MV and 15 MV photon beams using a Markus parallel-plate ionization chamber, GafChromic EBT3 film, and MOSFET detector for different field sizes and beam angles. The measurements were made in a water equivalent solid phantom at the surface and in the buildup region of the 6 MV and 15 MV photon beams at 100 cm source-detector distance for 5 × 5, 10 × 10, and 20 × 20 cm2 field sizes and 0°, 30°, 60°, and 80° beam angles. The surface doses using 6 MV photon beams for 10 × 10 cm2 field size were found to be 20.3%, 18.8%, and 25.5% for Markus chamber, EBT3 film, and MOSFET detector, respectively. The surface doses using 15 MV photon beams for 10 × 10 cm2 field size were found to be 14.9%, 13.4%, and 16.4% for Markus chamber, EBT3 film, and MOSFET detector, respectively. The surface dose increased with field size for all dosimeters. As the angle of the incident radiation beam became more oblique, the surface dose increased. The effective measurement depths of dosimeters vary; thus, the results of the measurements could be different. This issue can lead to mistakes at surface and buildup dosimetry and must be taken into account.